2005
DOI: 10.1248/cpb.53.402
|View full text |Cite
|
Sign up to set email alerts
|

N-Arylpiperazine-1-carboxamide Derivatives: a Novel Series of Orally Active Nonsteroidal Androgen Receptor Antagonists

Abstract: Prostate cancer has become the most common cancer among men, and the second leading cause of male cancer deaths in the United States.1) Testosterone and 5a-dihydrotestosterone are androgens that are required for the development of both the normal prostate and prostate cancer. 2)Androgens act through the androgen receptor (AR), which belongs to the steroid-receptor superfamily of ligand-dependent transcription factors.3,4) Both steroidal and nonsteroidal antiandrogens are available, and these molecules are of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The stable transfected cells were selected in the culture medium supplemented with neomycin. The selected clone was designated as AR/CHO#3 (human AR gene and MMTV luciferase reporter gene integrated CHO cell) or SV/CHO#10 (SV-40-luciferase reporter gene integrated CHO cell), respectively [31]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stable transfected cells were selected in the culture medium supplemented with neomycin. The selected clone was designated as AR/CHO#3 (human AR gene and MMTV luciferase reporter gene integrated CHO cell) or SV/CHO#10 (SV-40-luciferase reporter gene integrated CHO cell), respectively [31]. …”
Section: Methodsmentioning
confidence: 99%
“…The rats were sacrificed by excessive chloroform anesthesia 6 h after final dosing, and both their ventral prostates and seminal vesicles-coagulate glands were removed and weighed. The anti-androgenic activity was expressed as a percentage of inhibition of the TP effect (TP-treated rats were arbitrarily assigned a value of 0% and vehicle-treated rats a value of 100%) [31]. …”
Section: Methodsmentioning
confidence: 99%
“…In Vivo Evaluation of Antiandrogenic Activities in Castrated Immature Rats 22) Andorgen treated male Wistar rats were obtained from the Animal House Colony, Research Institute of Ophthalmology, Giza, Egypt. Prepubertal male rats aged 3 weeks were castrated by the scrotal route under ether anesthesia.…”
Section: -Oxo-3-cyano-6-(4-chlorophenyl)androst-4-ene[1716-c]pyran-mentioning
confidence: 99%
“…The derivative YM92088 ( 51 ; IC 50 =0.47 μ M ) exhibited greater potency as an in vitro AR antagonist than R ‐bicalutamide ( 2 ; IC 50 =0.89 μ M ). However, the in vivo activity was lower than that of R ‐bicalutamide ( 2 )—32 % and 75 % inhibition, respectively, and 51 was found to be metabolically unstable in human liver microsomes 42. A series of N ‐arylpiperazine‐1‐carboxamide derivatives of 51 (YM92088) were synthesized (compounds 52 – 55 );42 these modifications improved the inhibitory activity, the metabolic stability profile and the oral potency.…”
Section: Nonsteroidal Antiandrogensmentioning
confidence: 99%
“…However, the in vivo activity was lower than that of R ‐bicalutamide ( 2 )—32 % and 75 % inhibition, respectively, and 51 was found to be metabolically unstable in human liver microsomes 42. A series of N ‐arylpiperazine‐1‐carboxamide derivatives of 51 (YM92088) were synthesized (compounds 52 – 55 );42 these modifications improved the inhibitory activity, the metabolic stability profile and the oral potency. The biological data demonstrated that other alternative cyclic amines and ring expansion of the piperazine are unfavorable for AR antagonism.…”
Section: Nonsteroidal Antiandrogensmentioning
confidence: 99%